2022
DOI: 10.1002/ca.23980
|View full text |Cite
|
Sign up to set email alerts
|

Auricular surface morphology and surface area does not influence subchondral bone density distribution in the dysfunctional sacroiliac joint

Abstract: Background: The subchondral lamella of the sacroiliac joint (SIJ) auricular surface is morphologically inconsistent, varying inter-individually and side-dependently. These variations have been well documented, however, the morpho-mechanical relationship to sacroiliac joint dysfunction (SIJD) remains unstudied to date. Here, the bone mineralisation density of the iliac and sacral auricular surface subchondral endplate is compared between morphological subtypes, as well as in large and small surfaces, in a cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Datasets for patients CT‐OAM were acquired by means of a conventional clinical CT (SOMATOM as64 open, Siemens) according to previous studies (Poilliot et al, 2022 ; Poilliot, Tannock, et al, 2020 ). The slice thickness averaged 1.25 mm (0.98 resolution) for the patient datasets and 0.75 mm (average of 0.6 resolution) for the cadaveric specimens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Datasets for patients CT‐OAM were acquired by means of a conventional clinical CT (SOMATOM as64 open, Siemens) according to previous studies (Poilliot et al, 2022 ; Poilliot, Tannock, et al, 2020 ). The slice thickness averaged 1.25 mm (0.98 resolution) for the patient datasets and 0.75 mm (average of 0.6 resolution) for the cadaveric specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the role of the auricular surface in joint mobility and bipedal force transmission, some studies have looked into the influence of the morphological differences and placement of the auricular surfaces in relation to the bony anatomy (Brunner et al, 1991 ; Rana et al, 2015 ; Waldrop et al, 1993 ). However, few studies have looked into whether the general shape and size of the SIJ auricular is associated with SIJ pain and what differences there may be between sexes (Jesse et al, 2017 ; Nishi et al, 2020 ; Ou‐Yang et al, 2017 ; Poilliot et al, 2022 ). Furthermore, no study has yet looked into the influence of different morphologies, including shape and size of a joint, on the overall long‐term force transmission within the ‘healthy’ pelvis and what that might imply for the development of subsequent dysfunction or for the general function of the SIJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIJ, a large, irregularly shaped diarthroidal joint with cartilage surfaces, is the largest surface area joint in the body. Poilliot et al measured the surface area in patients with SIJ dysfunction and reported the dysfunctional cohort area averaged 15.0 ± 2.4 cm 29 . They concluded that larger joints are predisposed to develop pain, which may be due to the dysfunction of extracapsular joint structures, which take active part in pelvic load distribution.…”
Section: Anatomymentioning
confidence: 99%
“…The joint is also composed of bony anatomy and ligamentous components. The ilium and the sacrum articulate with a typically c-shaped surface 9-12 . There is variation in the number of segments, with there reliably being at least 2 segments.…”
Section: Anatomymentioning
confidence: 99%